2023
DOI: 10.1038/s41467-023-41943-x
|View full text |Cite
|
Sign up to set email alerts
|

Metal to non-metal sites of metallic sulfides switching products from CO to CH4 for photocatalytic CO2 reduction

Yao Chai,
Yuehua Kong,
Min Lin
et al.

Abstract: The active center for the adsorption and activation of carbon dioxide plays a vital role in the conversion and product selectivity of photocatalytic CO2 reduction. Here, we find multiple metal sulfides CuInSnS4 octahedral nanocrystal with exposed (1 1 1) plane for the selectively photocatalytic CO2 reduction to methane. Still, the product is switched to carbon monoxide on the corresponding individual metal sulfides In2S3, SnS2, and Cu2S. Unlike the common metal or defects as active sites, the non-metal sulfur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…The HO-Ru/TiN electrode affords a higher photocurrent generation than TiN (Figure S28a), mirroring the quicker charge transport of HO-Ru/TiN, which matches with its lower electronic resistance revealed by EIS (Figure S28b). Further, HO-Ru/TiN manifests a markedly reduced PL intensity than TiN (Figure S28c), reflecting the suppressed recombination of charge carriers on TiN after decorating Ru species . These outcomes confirm that HO-Ru/TiN maintains accelerated separation and transfer of the charge carriers to allow for CO 2 photoreduction.…”
Section: Resultsmentioning
confidence: 68%
“…The HO-Ru/TiN electrode affords a higher photocurrent generation than TiN (Figure S28a), mirroring the quicker charge transport of HO-Ru/TiN, which matches with its lower electronic resistance revealed by EIS (Figure S28b). Further, HO-Ru/TiN manifests a markedly reduced PL intensity than TiN (Figure S28c), reflecting the suppressed recombination of charge carriers on TiN after decorating Ru species . These outcomes confirm that HO-Ru/TiN maintains accelerated separation and transfer of the charge carriers to allow for CO 2 photoreduction.…”
Section: Resultsmentioning
confidence: 68%
“…Also, the potential versus the Ag/AgCl electrode was converted to the NHE scale using E (NHE) = E (Ag/AgCl) + 0.197 V (pH = 7) . Using the formula E g = E VB – E CB , , where E g represents the band gap, E VB signifies the valence band potential, and E CB denotes the conduction band potential, we can estimate that the CB potential for β-Ga 2 O 3 and the VB potential for CoGa 2 O 4 are estimated to be about −1.40 and 2.16 V (vs NHE), respectively. Thus, a possible band structure based on the p–n heterojunction can be formed in the CG/GO composite consisting of an n-type β-Ga 2 O 3 core and a p-type CoGa 2 O 4 shell.…”
Section: Resultsmentioning
confidence: 99%
“…2 It attracts broad research interest and has been demonstrated as a potential strategy to address energy crisis and environment problems. 2−13 Up to date, various kinds of catalysts such as metal−organic frameworks (MOFs), 3−5 metallic oxides, 6,7 metallic sulfides, 8,9 covalent organic frameworks (COFs), 10,11 and compounds 12,13 are developed to drive multielectron CO 2 reduction. However, the sluggish oxidation reaction (2H 2 O + 4h + → 4H + + O 2 ) triggered by photoexcited holes (h + ) greatly limited the photocatalytic activity of these photocatalysts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Artificial photosynthesis via coupling photocatalytic reduction of CO 2 with oxidation of H 2 O is a promising technology that can be used to convert solar energy into usable fuels and fine chemicals in a sustainable way . It attracts broad research interest and has been demonstrated as a potential strategy to address energy crisis and environment problems. Up to date, various kinds of catalysts such as metal–organic frameworks (MOFs), metallic oxides, , metallic sulfides, , covalent organic frameworks (COFs), , and compounds , are developed to drive multielectron CO 2 reduction. However, the sluggish oxidation reaction (2H 2 O + 4h + → 4H + + O 2 ) triggered by photoexcited holes (h + ) greatly limited the photocatalytic activity of these photocatalysts. Although sacrificial reagents can help to improve CO 2 reduction activity, the expenses should not be overlooked such as cost-push, whole energy dissipation, secondary pollution, etc .…”
Section: Introductionmentioning
confidence: 99%